Screening of Extracellular Enzyme from Phaeophyceae-Associated Fungi. Issue 1 (May 2021) - Ayuningtyas, E P; Sibero, M T; Hutapea, N E Br; Frederick, E H; Murwani, R; Zilda, D S; Wijayanti, D P; Sabdono, A; Pringgenies, D; Radjasa, O K
Abstract: Enzymes are known as a multipurpose catalyst and their potential through time. Various types of enzymes are widely utilized in fermentation and the pharmaceutical industry. One of the most potential enzyme producers is marine fungi, which can be isolated from seaweed. The purposes of this research were to isolate and screen seaweed-associated fungi that exhibited extracellular amylase. The fungi were isolated by tapping method on PDA medium and screened using starch agar, agarase, alginate, and carrageenan medium. Enzyme activity was detected by flooding the starch plates with iodine reagent. The presence of the inhibition zone around the colony indicated enzyme activity. Two potential isolates were identified as Penicillium oligosporum . and showed their activity in producing amylase, agarase, alginate lyase, and carrageenase.